Menyoal Gangguan Kesehatan Mental Deviasi Seksual Fetish - Hadyan Zulkaisi Sukoco; Faiq Althof; Ulin Nihayah (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This article aims to explain a dangerous form of sexual deviation where the perpetrator uses sexual gratification with sexually oriented inanimate or inanimate objects known as fetishes. Fetish behavior is a form of sexual deviation where the sexual activity carried out is carried out improperly to get sexual pleasure. This deviant behavior is very dangerous, because the perpetrators tend to use sexual objects that are unnatural or abnormal. Deviant sexual behavior if not above will lead to sexual behavior that is growing and even leads to prolonged stress. This is because the perpetrators cannot channel their deviant sexual desires and also have an impact on a person's mental health disorder. The research method used in writing this journal is a literature study based on case studies. The results of the analysis obtained data that fetish sexual deviation behavior in mental health can be treated through Islamic therapy to suppress deviations committed by perpetrators.